(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
A 11year-old girl was admitted in the Department of Paediatric Nephrology, National Institute of Kidney Diseases and Urology (NIKDU), Sher-E-Bangla Nagar, Dhaka. She was diagnosed as a case of nephrotic syndrome associated with primary hypothyroidism. She had short stature and was malnourished, but had no family history of hypothyroidism or renal diseases. She also had no consanguinity. She was treated with oral steroid and levothyroxin associated with nutritional support. Her condition improved with the treatment. At regular follow up her height and nutritional status was improved. Though hypothyroidism may be associated with nephrotic syndrome, it should be carefully evaluated. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i2.44 Chatt Maa Shi Hosp Med Coll J 2013; 12(2): 63-65